(untitled) (Praxis Educativa, 2025)
Studying at different educational levels requires the preparation of written texts that frequently present text fragments without referring to the authors incorrect or forms of citation, that is, plagiarism. Plagiarism is approached from the ethical, legal and textual dimension. The objective is to present the perspective of university students regarding this practice. A total of 129 students participated virtually. The analysis of the information was carried out with the Atlas ti program. The results highlight the recognition of the work and effort of the authors; the circumstances, temporality and educational level in which plagiarism has been committed. The conclusion, in agreement with several authors, is about the challenges faced by educational institutions at different levels to avoid plagiarism and encourage the writing of academic texts with original ideas, granting the corresponding credits.